Intraoperative dexmedetomidine use is associated with lower incidence of acute kidney injury after non-cardiac surgery - Yong-Zhong Tang; Qiong Wang; Li Zhi; Xing Liu; Yuan Le; Qin Liao; Bo Li; Wei Zhang (Renal Failure)
Background Previous studies have shown that perioperative dexmedetomidine could reduce the incidence of postoperative AKI in cardiovascular surgery, however, its effectiveness in the non-cardiovascular surgery patient population has not been reported. The aim of this study was to investigate the effect of intraoperative dexmedetomidine on the incidence of postoperative AKI and postoperative ICU admissions in patients undergoing non-cardiovascular surgery.Design and setting A single-center retrospective cohort study obtained from the database of the Center for Anesthesia and Surgery, the Third Xiangya Hospital.Patients Inpatients between 18 and 75 years of age who were admitted to our hospital for non-cardiovascular surgery from 2012 to 2019.Results Overall 2391 patients who used dexmedetomidine intraoperatively were analyzed in comparison to 4552 patients who did not use dexmedetomidine after one-to-two matching. The two cohorts had similar baseline values and demographic characteristics. The incidence of AKI was lower in patients with intraoperative dexmedetomidine use than in the nonuse group (OR 0.60, p < .001). The rate of severe renal failure needing dialysis was also lower than in the nonuse group (β = –0.02, p < .05). After adjusting for confounding factors, the rate of AKI was still lower in the dexmedetomidine group. The rate of postoperative ICU admissions and in-hospital deaths were similar in the two groups (p > .05).Conclusion For non-cardiovascular surgery patient population, intraoperative use of dexmedetomidine was associated with a lower incidence and less severity of postoperative AKI. However, there was no significant correlation with postoperative ICU occupancy or in-hospital mortality. Further prospective RCTs are needed in the future.